Pedagogical Implications of Linguistic Acculturation in the Process of Acquisition of the 2nd Language. From Theory to Practice - Polok, Krzysztof (Glottodidactica, 2006)
At present there are many different forms and techniques of teaching and learning a language whose aim is to aid all the teacher’s activities s/he has planned while attempting to bring the language lessons as close to the authentic core of the language as possible that any teacher who really cares for the quality of his lessons can do whatever he only wants to incorporate the forces of authentic language contact to the classroom language behaviour of his/her pupils.